2023
DOI: 10.3390/polym15122679
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Natural Biopolymer for Enhanced Surface, Physical and Mechanical Properties of Glass Ionomer Luting Cement

Abstract: This laboratory investigation aimed to synthesize and characterize micron-sized Gum Arabic (GA) powder and incorporate it in commercially available GIC luting formulation for enhanced physical and mechanical properties of GIC composite. Oxidation of GA was performed and GA-reinforced GIC in 0.5, 1.0, 2.0, 4.0 & 8.0 wt.% formulations were prepared in disc-shaped using two commercially available GIC luting materials (Medicem and Ketac Cem Radiopaque). While the control groups of both materials were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…Therefore, assessing the compressive strength becomes crucial when modifying GIC. In this study, the compressive strength characteristics of Acacia nilotica-modified GIC were significantly higher than conventional GIC, aligning with the findings of Khan et al, who stated that the addition of gum arabic from Acacia seyal to GIC powder (luting cement) resulted in increased compressive strength characteristics [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, assessing the compressive strength becomes crucial when modifying GIC. In this study, the compressive strength characteristics of Acacia nilotica-modified GIC were significantly higher than conventional GIC, aligning with the findings of Khan et al, who stated that the addition of gum arabic from Acacia seyal to GIC powder (luting cement) resulted in increased compressive strength characteristics [29].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, assessing the compressive strength becomes crucial when modifying GIC. In this study, the compressive strength characteristics of Acacia nilotica -modified GIC were significantly higher than conventional GIC, aligning with the findings of Khan et al, who stated that the addition of gum arabic from Acacia seyal to GIC powder (luting cement) resulted in increased compressive strength characteristics [ 29 ]. The increased compressive strength can be credited to Acacia nilotica , which harbors water-soluble polysaccharides capable of creating hydrogen bonds with the polyacrylic acid constituent of the cement.…”
Section: Discussionsupporting
confidence: 89%
“…In our previous study, GA was successfully oxidized and incorporated into GICs at weight ratios of 0.5 and 1.0 wt.%. We observed that oxidation resulted in the formation of various acid groups, including but not limited to glucuronic acid, galacturonic acid, glucaric acid, and guluronic acid, both in small and large molecular structures and resulted in improved mechanical properties of the GIC luting material, including nano hardness, elastic modulus, compressive strength, and diametral tensile strength [ 19 ]. The observed enhancements in compressive strength, diametral tensile strength, and elastic modulus of 0.5 and 1.0 wt.% GA–GIC formulations provided substantial motivation to persist with further investigation in this research endeavor.…”
Section: Discussionmentioning
confidence: 99%
“…One of the promising methods to improve the physical and mechanical properties of GIC composites is the introduction of various types of admixtures. In work [ 11 ], the authors enriched the GIC cement preparation with micrometric gum arabic (GA) powder of various concentrations using two commercially available GIC cement materials (Medicem and Ketac Cem Radiopaque). It was found that the inclusion of oxidized GA powder in the GIC formulation helps to improve mechanical properties with a slight increase in water solubility and sorption parameters.…”
Section: Introductionmentioning
confidence: 99%